Analysis Of The Influence Of Transactional And Transformational Leadership On Organizational Effectiveness Mediated By Organizational Culture - Mujiatun, Mujiatun; Hadi, Syamsul; Lukitaningsih, Ambar (Sekolah Tinggi Ilmu Ekonomi Amkop Makassar, 2025)
This study explores the influence of transactional and transformational leadership on organizational effectiveness, with organizational culture serving as a mediating variable, aiming to examine how leadership styles shape culture and subsequently impact effectiveness, particularly within public sector institutions. It offers a novel contribution by emphasizing the mediating role of organizational culture in the relationship between leadership styles and organizational effectiveness—an area that has been inconsistently addressed in previous research. By focusing on a governmental office (Office X), the study provides contextual insights into leadership dynamics in public administration. The findings reveal that transactional leadership has a positive and significant effect on organizational culture, which in turn enhances organizational effectiveness. In contrast, transformational leadership, while positively correlated with organizational effectiveness, does not significantly influence organizational culture directly. Furthermore, organizational culture significantly mediates the relationship between transactional leadership and organizational effectiveness, but this mediating role is not supported in the case of transformational leadership. The study concludes that transactional leadership is more effective within established organizational cultures, whereas transformational leadership is better suited to innovative and collaborative environments. Thus, organizational culture is crucial in enhancing leadership effectiveness, and future research should consider additional mediating factors such as employee motivation and job satisfaction.